ANALISIS PENERAPAN SAK EMKM PADA LAPORAN KEUANGAN USAHA MIKRO, KECIL DAN MENENGAH DI JAMBI KOTA SEBERANG - Fadia Ardhina; Rico Wijaya; Riski Hernando (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
This study aims to find out how the application of Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) to Jambi Ariny Batik Crafts, this background makes this business interesting to study in order to find out which use of financial statements is based on the application of Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM) carried out on these Micro, Small and Medium Enterprises (UMKM) and what factors caused the recording of financial reports based on SAK EMKM on these MSMEs. This research was conducted using a qualitative method that leads to the description and application of financial records based on Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). The data in this study are primary data and secondary data by conducting interviews and taking financial reports to be processed to comply with SAK. EMKM. The results of this study indicate that the financial recording system is carried out manually only based on disbursements and cash receipts and is still very simple so that it shows that financial reports are made with criteria that are not good to low and the factors that cause the failure of SAK EMKM in the Jambi Ariny Batik Crafts business are due to internal factors in the form of a lack of understanding of the importance of financial reports in running a business based on SAK EMKM, discipline and human resources, while external factors are due to a lack of supervision from stakeholders who have an interest in financial reports